Ethics Research in Environmental Education - Bob Jickling (Environmental Association of Southern Africa, 2005)
This paper takes a research orientation towards ethics and, in so doing, frames ethics as processes of inquiry and stories to be told. First, it explores ways that ethics might be 'reimagined', situated in everyday contexts and interpreted in ways that allow its stories to do work and invite readers and listeners to consider ethics. Second, it creates some openings to imagine ethics as a series of re-constructive experiments. Finally, this paper is an invitation to engage in 'ethics research' within environmental education.